Optimalisasi Performance Operator Service Sepeda Motor Dengan Menggunakan Metode Work Sampling Pada UMKM Giant Jaya Motor - Panggabean, Tri Agus M; Harahap, Uun Novalia; Utama, Denny Walady (CV. IRA PUBLISHING, 2024)
Motorcycles are a convenient mode of transportation for daily activities. The Giant Jaya Motor motorcycle repair shop, a small and medium-sized enterprise (SME), operates in sales, repair services, maintenance, and spare parts supply. Efficient maintenance and repair services are crucial for smooth operations. The workload at the Giant Jaya Motor workshop is very high, and the operators often need more time to rest, leading to decreased performance and wasted time during services. This study aims to determine the standard time and workload of the operators using the Work Sampling method. This method, similar to a stopwatch time study, is classified as direct work observation because the measurement activities are carried out at the actual workplace being studied. The data processing results show that the standard time required to service one motorcycle is 26.34 minutes, with a working time percentage of 89.41%. It is recommended that the Giant Jaya Motor workshop organize a more efficient work schedule to provide sufficient rest time for operators to reduce fatigue and improve performance. Additionally, improving time management and providing training for operators can reduce time waste and increase overall productivity. Implementing more efficient technology or tools can also speed up maintenance and repair processes without compromising service quality.